Exogenous oxytocin increases gaze to humans in male cats - Hattori, Madoka; Kinoshita, Kodzue; Saito, Atsuko; Yamamoto, Shinya (Scientific Reports, 2024)
Although oxytocin (OT) plays a role in bonding between heterospecifics and conspecifics, the effects of OT on the formation of such interspecific social behavior have only been investigated between humans and dogs ( Canis familiaris ). In this study, for comparative evaluation of the effects of OT between dog–human and cat–human social interaction, we investigated the effects of exogenous OT on the behavior of domestic cats ( Felis silvestris catus ) toward humans. We intranasally administered OT or saline to 30 cats using a nebulizer and recorded their behavior (gaze, touch, vocalization, and proximity). The results showed an interaction between the administration condition and sex for gaze duration. Post hoc analyses revealed a significant increase in gaze in the OT condition in male cats but not in females. There were no significant differences in gaze toward owners and strangers in any condition or sex. The male-specific OT-mediated increase in gaze toward humans observed in this study differs from previous research on dogs wherein such effects were observed only in females. These findings suggest an overall effect of exogenous OT on cats’ social relationship with humans as well as the possibility of different mechanisms between cat–human and dog–human relationships.